Humor in Translation: An Analysis of Johnny English Reborn - Azzura Firda Alfian; Baharuddin Baharuddin; Lalu Ali Wardana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
This study examines the translation of humor in the film Johnny English Reborn from English into Indonesian subtitles. The purpose of the study is to analyze the construction of humor through violations of Grice's maxims and to identify Newmark's translation strategies used to maintain the comedic effect. The method applied is qualitative descriptive with an analysis of 28 humorous dialogue quotations and their translations. The results show that humor is constructed primarily through violations of the maxims of Quality and Relation, creating irony and wordplay. In translation, the Communicative and Faithful strategies are most dominant, successfully preserving the humorous intent while adapting to Indonesian cultural norms. In conclusion, effective humor translation requires a balance between pragmatic recognition of maxim violations and strategic linguistic adaptation, contributing both theoretically and practically to the field of audiovisual translation.